Character Development of Celengan Movements in Jaranan Turonggo Yakso : within the Dance Piece Tomak Through the Use of Dramatic Dance - Valen, Gymanstiar; Sasanadjati, Jajuk Dwi (Solah, 2025)
The dance work Tomak is an exploration and development of the celengan segment in the traditional Jaranan performance, approached through the form of dramatic dance. This piece emphasizes the characteristic movements of celengan, which are developed into dramatized forms within a folk performance framework. The choreographer expands upon movements such as budalan, gejug gantung, nyruduk ngiwa nengen, sengkrak pundak, and perangan. The creation of this work adopts Jacqueline Smith’s Construction Method 1, which includes several stages: initial stimulus, dance type, mode of presentation, improvisation, evaluation, refinement/selection, and motif development. The primary references include Kala Srenggi (produced by the Trenggalek Department of Tourism and Culture) and Body of Evolution (by Ari Chandra Pamungkas, 2023). Theoretical frameworks used in this creation are the choreographic theory by Sal Murgiyanto, developmental theory by Soedarsono, and the construction method by Jacqueline Smith. The structure of the performance follows a double-cone dramatic design, consisting of six parts: an introduction, four scenes, and a closing section. Supporting elements such as costume and makeup, lighting design, and musical accompaniment contribute to the overall presentation. Tomak aims to provide space for innovation in traditional arts and to inspire young generations and artists to preserve and develop cultural heritage through fresh, communicative performance formats.